(untitled) (International Journal of Business, Economics and Management, 2016)
This study is an exploratory study that aims to examine the impact of workgroup emotional climates on group effectiveness in Egypt. The paper contains a review of literature on the concept of workgroup emotional climate. The study findings reveal that workgroup emotional climate is correlated with group effectiveness. These findings open up new questions to be explored by future research.